Sporadic Burkitt Lymphoma Presenting as Acute Pancreatitis, Concurrent Sinusitis, and Enlarged Adenoids - Vasudha Mahajan; You-Wen Qian; Brooke Blake; Yesenia Rojas-Khalil; Ravi S. Radhakrishnan; Akila Muthukumar (Hindawi Limited, 2016)
Pancreatitis and sinusitis as presentations of Burkitt lymphoma are uncommon and rarely described in children. We describe here the case of a child who presented with symptoms suggestive of sinusitis unresponsive to antibiotics, with subsequent development of abdominal symptoms due to pancreatitis. He was eventually diagnosed with Burkitt lymphoma.